The Mineralization and Structural Geology of the Porphyry Copper Deposits of Pakistan - Shah, Syed Tallataf Hussain; Khan, Nangyal Ghani; Abbasi, Muhammad Imran Hafeez; Tabassum, Kamran; Shah , Syed Khaizer Wahab (Nepal Journal of Science and Technology, 2021)
The purpose of this review is to shed light on copper deposits found in different regions of Pakistan. The geological attributes of copper deposits have been considered with their tectonic context. The porphyry copper deposits can be traced in Pakistan from the north through Kohistan Island Arc (KIA) up to the south to Chaghi Magmatic Arc (CMA). These deposits are mainly found in and around the Late Tertiary–Early Tertiary Himalayan Belt, Kohistan magmatic arc, Karakorum Block Foreland fold and thrust belt, Ophiolite Thrust belt, Suture zone and Chaghi Magmatic Arc. These deposits in Pakistan are chiefly established in different episodes of tectonic regimes, including subduction processes, oceanic island arc, continental arc, along with Chaman- OrnachNal Fault system and post-collisional settings.